Genetic diversity of freshwater fishes from the South American Atlantic Rainforest: The case study of the genus Phalloceros. (December 2015) - Amaral, C.R.L.; Maciel, V.A.; Pereira, F.; Mazzoni, R.; Silva, D.A.; Amorim, A.; Carvalho, E.F.
Abstract: The Atlantic Rainforest is one of the global conservation hotspots, representing a highly threatened area with elevated levels of endemism and species richness. Fish species from this area are one of the most exploited vertebrate groups by the international aquarium trade, an industry with an annual trade volume of about U15–25 billions. The native South American genus Phalloceros includes species commonly known as "guppies", being found not only in South America, but also New Zeeland, Australia and Malawi, where they have been secondarily introduced with several ecological effects. We used SNPs and indels in mitochondrial DNA (mtDNA) to investigate the molecular diversity of the species Phalloceros anisophallos from coastal Atlantic drainage areas in Rio de Janeiro state, Brazil. Our aim is to develop a panel of mitochondrial markers to be used for the identification of guppy fish species. The molecular analyses were carried out using novel ( n = 28) sequences from the mitochondrial COI gene (for DNA Barcoding) and the 16S rDNA gene (for SPInDel). We were able to determine the molecular variability of the distinct populations of P. anisophallos, which showed distinct patterns of shared polymorphism.